2005
DOI: 10.1002/elps.200410213
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of virtual two‐dimensional gels based upon affinity capillary electrophoresis hyphenated to ion trap‐mass spectrometry

Abstract: Affinity capillary electrophoresis (ACE) is a robust tool for the study of noncovalent biomolecular interactions and to determine the binding constants. It is advantageous due to the speed of analysis, the high and reproducible separation efficiencies, the low consumption of analytes, the ability to study several interactions at the same time, and to cover a wide range of affinity. The use of an ion trap-mass spectrometer as a sensitive and specific detector, coupled on-line with a classical UV detector, permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…One may predict that the coupling of ACE methods with MS, so far used rarely and only for model studies [112,113], will increase. In complex, multi-component equilibriums, the qualitative identification power of MS will be more important the more partners there are in the complex.…”
Section: Discussionmentioning
confidence: 99%
“…One may predict that the coupling of ACE methods with MS, so far used rarely and only for model studies [112,113], will increase. In complex, multi-component equilibriums, the qualitative identification power of MS will be more important the more partners there are in the complex.…”
Section: Discussionmentioning
confidence: 99%
“…Advances have recently been reviewed [115,116]. The challenge of CE-MS remains the development of suitable interfaces that allow the separation buffer conditions of CE to be compatible with the ionization process of MS. Machour et al [117] employed IT-MS as a parallel detector to UV in studying mobility shifts induced by the interaction of vancomycin derivatives with dipeptide substrates. It was concluded that CE-MS is a valuable tool by combining affinity separation with accurate mass determination, but it was found that binding constants could only be reliably calculated in this system based on the CE-UV data.…”
Section: Technical Innovationmentioning
confidence: 99%
“…Among the multiple methods affording the binding constant determination by CE, ACE is the most popular [33]. The broad applicability of ACE is illustrated by a variety of studies on biomolecular interactions, involving peptide-drug [34], protein-polysaccharides [35][36][37], peptide-polymers [38], drug-CDs [39,40], and protein-nucleic acid [41,42]. Although several reports have been published regarding the analysis of dendrimers [43][44][45][46][47][48] or VIP [49,50] using CE, to date, no work has reported the use of ACE to study the molecular interactions between this peptide and PAMAM dendrimers.…”
Section: Introductionmentioning
confidence: 99%